2002
DOI: 10.1002/jez.90006
|View full text |Cite
|
Sign up to set email alerts
|

In vivo transfection of the mouse vas deferens

Abstract: To explore the possibility that specific characteristics of the epithelium of the male tract can be modified, transfections of the mouse vas deferens have been performed using in vivo injections of cationic DNA/liposome complexes. Gene transfer was done employing the reporter genes pEGFP-C1 encoding Green Fluorescent Protein (GFP) and pCMV-nls-beta encoding the nuclear beta-Galactosidase (beta-Gal). Foreign gene expression reached a maximum of 6.8% in the epithelial cells of the vas after treatment with the nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…Type A spermatogonia are the only immortalized diploid cells that are reproduced in adult male animals, including mice, and they have a high self-renewal capacity and pluripotent potential (34,35). On that basis, and following consideration of the results of the present study along with those of Shen et al (26) and Valenzuela et al (28), it was suggested that the TMGT mechanism may include additional components. Once a foreign DNA and liposome (DOTAP) complex is injected directly into the testis, all cells that have contact with that complex, not only spermatids at different development stages, but also the two types of spermatogonia are considered to be transfected with foreign DNA.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Type A spermatogonia are the only immortalized diploid cells that are reproduced in adult male animals, including mice, and they have a high self-renewal capacity and pluripotent potential (34,35). On that basis, and following consideration of the results of the present study along with those of Shen et al (26) and Valenzuela et al (28), it was suggested that the TMGT mechanism may include additional components. Once a foreign DNA and liposome (DOTAP) complex is injected directly into the testis, all cells that have contact with that complex, not only spermatids at different development stages, but also the two types of spermatogonia are considered to be transfected with foreign DNA.…”
Section: Discussionsupporting
confidence: 50%
“…Sato et al (27) also obtained F2 transgenic-positive animals. However, Shen et al (26) and Valenzuela et al (28) did not identify transgene-positive individuals in an F2 generation. We hypothesize that the transgenic positive rate in F2 offspring is associated with the age at which the F1 parents are mated; the younger the F1 parent, the higher the F2 transgenic positive rate; when the F1 parent ages, the F2 transgenic positive rate decreases.…”
Section: Discussionmentioning
confidence: 98%
“…The effect of inflammatory mediators is blocked, perhaps by the same kininase enzyme or other carboxypeptidase (Valenzuela et al, 2002).Tick salivary kininase, for example dipeptidyl carboxypeptidase from I. scapularis tick saliva (Ribeiro and Mather, 1998), hydrolyzed circulating kinins (e.g. bradykinin).…”
Section: Hard Ticks Vs Inflammation and Immunitymentioning
confidence: 99%
“…Besides inhibition of the production of pro-inflammatory cytokines, IL-6, and TNF-α (Leboulle et al, 2002b) and anti-haemostatic effects mentioned above (Prevot et al, 2006), Iris has been shown to suppress T cell proliferation and induces Th2 type immune response. Due to sialotranscriptome work on I. scapularis saliva (Valenzuela et al, 2002), a large number of protease inhibitors was detected in SG, including secreted 12.5 kDa Sialostatin L containing the conserved cystatin domain. It inhibits papain-like cysteine proteases, targeting mainly cathepsin L, C and S. This protein displays an anti-inflammatory effect and reduces the proliferation of cytotoxic T lymphocytes (CTL) (Kotsyfakis et al, 2006), as well as antigen specific CD4 + T cells (Sa-Nunes et al, 2009).…”
Section: Hard Ticks Vs Inflammation and Immunitymentioning
confidence: 99%
“…In the male genital tract in vitro transfections have been developed using epididymal cell lines (Kirchoff et al, 2004;Dufresne et al, 2005;Yu et al, 2006). In the mouse, the vas deferens was in vivo transfected using the GFP gene construction (Valenzuela et al, 2002). In the human an in vitro transfection of the vas was also undertaken (Esponda et al, 2004).…”
Section: Introductionmentioning
confidence: 99%